2003
DOI: 10.1002/cncr.11594
|View full text |Cite
|
Sign up to set email alerts
|

Heat shock proteins HSP27, HSP60, HSP70, and HSP90

Abstract: BACKGROUND Heat shock proteins (HSPs) are synthesized by cells in response to various stress conditions, including carcinogenesis. The expression of HSPs in neoplasia has been implicated in the regulation of apoptosis, and HSPs also can act by increasing immunity. In the current study, the authors attempted to clarify the significance of HSPs in bladder carcinoma and their effect on tumor behavior. METHODS Expression levels of the 27‐kilodalton HSP (HSP27), HSP60, HSP70, and HSP90 were studied using immunohist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
48
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 149 publications
(51 citation statements)
references
References 44 publications
2
48
1
Order By: Relevance
“…Hsp90 is a molecular chaperone that promotes proper folding and stability of several classes of proteins. Hsp90 expression is increased in several cancer types including melanoma [6,16]. N-terminal Hsp90 inhibitors have been used to target melanoma cells [17,18].…”
Section: Discussionmentioning
confidence: 99%
“…Hsp90 is a molecular chaperone that promotes proper folding and stability of several classes of proteins. Hsp90 expression is increased in several cancer types including melanoma [6,16]. N-terminal Hsp90 inhibitors have been used to target melanoma cells [17,18].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, positive HSP60 expression in esophageal squamous cell carcinoma (15) as well as ovarian cancer (28) correlates with good prognosis for the patients. By contrast, loss of HSP60 expression is associated with the risk of developing an infiltrating recurrent bladder cancer (29). These observations suggest a pro-apoptotic and beneficial effect of HSP60 in these cancer cells in vivo.…”
mentioning
confidence: 83%
“…However, Kirchhoff et al 17 showed that cytosolic HSP60 played an anti-apoptotic role in cardiac myocytes through interactions with pro-apoptotic Bax and Bak proteins that were also considered as an important factor in preventing apoptosis in tumor cells. As the result, HSP60 was down-regulated in bronchial adenocarcinoma, vesical transitional cell carcinoma and carcinosarcoma18192021 whereas the high HSP60 expression was presented in cervical cancer, prostate cancer, breast cancer and GBM22232425.…”
mentioning
confidence: 96%